(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Metallic nanoparticles (MNP) have captivated scientist for over a century and are now profoundly utilized in biomedical sciences and engineering. MNPs interact with key cellular organelles and biomolecules, including DNA, enzymes, ribosomes, and liposomes, which can have an impact on gene expression, oxidative stress, protein and enzyme activation, and cell membrane permeability. It has been shown that the cellular metabolites of living organisms like bacteria, yeast, fungi, and plant cells can convert inorganic metal ions into metal NPs. By utilizing biological agents in green chemistry, metallic nanoparticles are produced that have less adverse effects and are more effective against cancer cells. These nanoparticles can physically infiltrate cancer cells and kill them by activating a variety of biochemical pathways, including apoptosis, necrosis, and autophagy. This review focuses on metal nanoparticles (copper, gold, and silver) and their usefulness in treating endemic diseases including cancer, hepatitis, and malaria. In the near future, metal NPs may also be a successful and affordable alternative for treating drug-resistant bacterial infections.